Myanmar Agricultural Performance Survey Round Five: Note on Sample Characteristics and Weighting - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2025)
The Myanmar Agricultural Performance Survey (MAPS) is a nationally and sub-nationally representative phone survey with the objective of collecting bi-annual data on agricultural indicators including crop production and sales, input use, crop marketing, farm and livestock assets, and farm services. The Myanmar Household Welfare Survey (MHWS) is a nationally and sub-nationally representative phone survey with the objective of collecting bi-annual data on household and individual welfare indicators, including poverty, food security, dietary quality, subjective wellbeing, and coping strategies. MAPS is a sub-sample survey that includes farming households from MHWS. There are five Rounds of MAPS. MAPS Rounds 1, 3, and 5 were conducted between January and March 2022 and 2024 and collect recall data on monsoon production. MAPS Round 2 and 4 were conducted between June and September 2022 and 2023 and collect recall data on dry season production (pre/post monsoon season).